Solar Lighting - Pode, Ramchandra; Diouf, Boucar; SpringerLink (Online service) (London : Springer London, 2011)
Limited availability of grid-based electricity is a major challenge faced by many developing countries, particularly the rural population. Fuel-based lighting, such as the kerosene lantern, is widespread in these areas, but it is a poor alternative, contributing to global warming and causing serious health problems. Several developing countries are therefore now encouraging the use of sustainable lighting. Solar Lighting gives an in-depth analysis of energy-efficient light production through the use of solar-powered LED systems. The authors pay particular attention to the interplay between energy transformation and device efficiency. They also discuss diverse aspects of renewable energy, including how an improvement in the efficiency of appliances can reduce the cost of energy. Solar Lighting is written for physicists, environmental experts and lighting engineers. It is also suitable for undergraduate students in the fields of environmental science, electrical engineering and renewable energy.
1. Why Clean Energy -- 2. Solar Photovoltaic Electricity -- 3. Light Emitting Diodes -- 4. OLED Lighting Technology -- 5. Acceptability of Solar Powered LED Lighting.
Keywords: Engineering; Engineering economy; Renewable energy sources; Sustainable development; Engineering; Renewable and Green Energy; Engineering Economics, Organization, Logistics, Marketing; Sustainable Development; Renewable and Green Energy